Long-term trends of alanine aminotransferase levels among persons living with human immunodeficiency virus/hepatitis B virus with and without hepatitis delta coinfection - Begré, Lorin; Béguelin, Charles; Boyd, Anders; Peters, Lars; Rockstroh, Jürgen; Günthard, Huldrych F.; Bernasconi, Enos; Cavassini, Matthias; Lacombe, Karine; Mocroft, Amanda; Wandeler, Gilles; Rauch, Andri (Frontiers in Medicine, 2022)
Background Hepatitis delta virus (HDV) infection accelerates the progression of liver disease in persons living with HIV and hepatitis B virus (HBV) coinfection. We explored the association between HDV infection and alanine aminotransferase (ALT) elevation during tenofovir-containing antiretroviral treatment among persons living with HIV/HBV. Materials and methods We included persons living with HIV/HBV with and without HDV starting tenofovir-containing antiretroviral therapy (ART) in three European cohorts with at least 18 months of follow-up. We defined HDV infection as a positive anti-HDV antibody test. We assessed risk factors for ALT elevation ≥ 1.25x upper limit of normal after 5 years of tenofovir-treatment using multivariate logistic regression models. The difference in ALT trends between individuals with and without HDV was evaluated using linear mixed effects models. Results 61/518 (11.8%) participants had an HDV infection. Among individuals with HDV, 63.9% had ALT elevation after 2 years and 55.6% after 5 years of tenofovir, whereas the estimates were 34.1% after two and 27.0% after 5 years in those without HDV. HDV coinfection (adjusted odds ratio 2.8, 95% confidence interval 1.4–5.8) and obesity at baseline (adjusted odds ratio 3.2, 95% confidence interval 1.2–8.0) were associated with ALT elevation after 5 years of tenofovir therapy. Mean ALT levels were consistently higher during follow-up in participants with HDV compared to those without HDV. Conclusion Persistent ALT elevation is common in persons living with HIV/HBV in Europe despite adequate HBV therapy. HDV coinfection and obesity are independent risk factors for persistent ALT elevation during long-term tenofovir treatment.